Determinasi Customer Loyalty: Peran Service Quality dan Customer Experience dengan Mediasi Customer Satisfaction - Febri Arisandi; Meylani Tuti; Etty Nurwati (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effects of Service Quality and Customer Experience on Customer Loyalty, with Customer Satisfaction serving as a mediating variable among customers of PT. Asrinda Arthasangga Reinsurance Brokers. The study is motivated by the importance of service quality and customer experience in creating customer satisfaction and fostering customer loyalty within the reinsurance brokerage industry, which emphasizes long-term business relationships. A quantitative approach with a causal research design was employed. Primary data were collected through questionnaires distributed to 250 respondents representing client companies of PT. Asrinda Arthasangga Reinsurance Brokers, selected using a purposive sampling technique. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results indicate that Service Quality has a positive and significant effect on Customer Satisfaction (t-statistics = 6.806 > 1.96) and Customer Loyalty (t-statistics = 5.454 > 1.96). Customer Experience also has a positive and significant effect on Customer Satisfaction (t-statistics = 4.785 > 1.96) and Customer Loyalty (t-statistics = 8.166 > 1.96). Furthermore, Customer Satisfaction has a positive and significant effect on Customer Loyalty (t-statistics = 5.666 > 1.96). The mediation analysis reveals that Customer Satisfaction partially mediates the effect of Service Quality on Customer Loyalty (t-statistics = 4.354 > 1.96), as well as the effect of Customer Experience on Customer Loyalty (t-statistics = 3.778 > 1.96). These findings suggest that improving service quality and customer experience in ways that enhance customer satisfaction constitutes an important strategy for strengthening customer loyalty in reinsurance brokerage service companies.